Sprouting of pre-sprouted sugarcane seedlings and micrometeorological variables under photo-selective nets - José J. F. Cordeiro Júnior; Cristiane Guiselini; Héliton Pandorfi; Alex S. Moraes; Dimas Menezes; Luiz A. de Almeida Neto (Revista Brasileira de Engenharia Agrícola e Ambiental)
ABSTRACT Sugarcane is a grass species that stands out worldwide in the production of ethanol. Brazil is the world’s largest producer and leader in exports, responsible for more than 50% of the products that are marketed worldwide. The objective of this study was to investigate the effect of photo-selective nets on micrometeorological variables and on sprouting of pre-sprouted sugarcane seedlings. The experiment was carried out in a protected environment at Universidade Federal Rural de Pernambuco - UFRPE, in a completely randomized design. Seedlings of cultivar RB92579 were obtained by the technique of production of pre-sprouted seedlings. The protected environment was divided into four modules corresponding to the treatments: covered with anti-UV low-density polyethylene plastic: + Solpack® red ultranet net, + Solpack® white net, + Solpack® freshnet net and without shade net. Micrometeorological data of air temperature and substrate temperature were recorded in each module. The first count of emergence, sprouting speed index and sprouting percentage were calculated. Principal component analysis was used to verify the association between the cultivation modules and the micrometeorological and sprouting variables of the seedlings. Air temperature in the protected environment was 8.7% higher than that in the external environment. The white net led to sprouting of 78.93%. The substrate temperature above 30.4 °C favored seedling sprouting. The modules with white net and red ultranet net favored seedling sprouting.